Pengaruh Penggunaan Medication Aids terhadap Tingkat Ketaatan Pasien Peptik Ulkus di Rumah Sakit Umum Daerah Arifin Achmad Provinsi Riau - Aryani, Fina; Muharni, Septi; Harahap, Yudina Awaliyah (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Peptic ulcer is a disease which characterized by injury of gastrointestinal tract due to the high production of acids and pepsin because of Helicobacter pylori infection, NSAIDs and stress. The recommendation for its therapy depends on the cause of the ulcer. It takes eight weeks for the treatment and patient is required to be obedient in taking the drug. An effort to improve patient compliance is by using medication aids. The purpose of this study is to determine the effect of medication aids on the level of adherence in treatment of ulcer peptic patients in Riau. Medication aids used are pill reminder containers and disposable packaging. This research used quasi experiment method, with Non-Randomized Control Group Pretest and Posttest Design which was done on 60 patients grouped into 30 control group patients and 30 treatment group patients during May - July 2017. Accidental sampling method that meets the inclusion criteria of ultrasound peptic patients caused by NSAIDs, 18 years old and willing to be a respondent. Data collection of patient compliance using standard questionnaires namely Morisky Medication Adherence Scale 8 (MMAS-8). Thedata were analyzed using Mann-Whitney statistic test. The results showed that p = 0,000 (p <0,05), meaning that there is influence of medication aids on the level of obedient peptic ulcer patient.